Distribution of 5-HT1F Receptors in Monkey Vestibular and Trigeminal Ganglion Cells - Usman, Habiba O.; Balaban, Carey D. (Frontiers in Neurology, 2016)
Background Evidence of serotonergic involvement in vestibular pathway contributions to migraine and balance disorders is compelling. Serotonergic 5-HT1B and 5-HT1D receptors are expressed extensively in inner ear ganglia of monkeys and rats. The serotonergic 5-HT1F receptor is also a target of triptans. This study describes its distribution in vestibular and trigeminal ganglia of monkeys. Methods Using primary polyclonal antibodies raised against oligopeptides specific for the human 5-HT1F receptor, neuronal somatic area and intensity of immunoreactive vestibular and trigeminal ganglia were quantified. Results and Discussion Virtually all vestibular and considerable trigeminal ganglia showed positive 5-HT1F receptor immunoreactivity. Inferior and superior vestibular ganglia staining appeared confined to distinct cell regions, varying considerably among cells of different sizes: more intense in small, punctate in some medium and regionally polarized in some large cells. Analyses of average somatic vestibular neuronal immunoreactive intensity identified mainly medium sized cells with high standard deviation of intensity corresponding to punctately stained cells. Less variability occurred in somatic intensity staining and cellular distribution among 5-HT1F receptor immunopositive trigeminal ganglia. Most exhibited similar punctate staining patterns, higher mean somatic immunoreactive intensity and larger neuronal somatic size proportions per size distribution subpopulation compared to vestibular ganglia size distribution populations. Centrally directed vestibular ganglion neuronal processes, cochlear inner hair cells, vestibular hair cells and blood vessels in vestibular maculae and cristae were immunoreactive. The 5-HT1F receptor expression in vestibular ganglia shows complex variable staining intensity patterns associated with cell size of immunopositive neurons, not seen in immunopositive trigeminal ganglia and not previously evident with 5-HT1B and 5-HT1D receptor subtype immunoreactivity in vestibular ganglia. These data motivate exploration of 5-HT1 receptor oligomerization and ligand functional selectivity in differential serotonergic involvement in co-morbidity of migraine and balance disorders. Similar findings in cochlear inner hair cell afferents are applicable to migraine-related tinnitus or hypercusis (phonophobia).